Pharmacokinetics of intermittently administered intravenous foscarnet in the treatment of acquired immunodeficiency syndrome patients with serious cytomegalovirus retinitis. - Aweeka, F (1989)
Foscarnet has been shown to be active in vitro against the human immunodeficiency virus and all human herpesviruses including cytomegalovirus (CMV). A pharmacokinetic study was carried out as part of a clinical trial designed to evaluate the safety and efficacy of intermittently administered intravenous foscarnet for the treatment of CMV retinitis. Eight patients with acquired immunodeficiency syndrome and serious CMV retinitis received 2-h intravenous infusions of foscarnet at a dosage of 60 mg/kg of body weight every 8 h for 14 days. Serial plasma samples were collected on days 3 and 14 of therapy, and foscarnet concentrations were determined by high-pressure liquid chromatography. On day 3 of therapy, the mean (+/- standard deviation) peak and trough levels in plasma were 509 (200) and 98 (29) microM, respectively, while on day 14 levels were 495 (149) and 126 (59) microM. The mean clearance in plasma on days 3 and 14 were 1.9 (0.6) and 1.7 (0.9) ml/min per kg, respectively. On day 14, the mean half-life was 4.5 (1.2) h and the volume of distribution was 0.74 (0.60) liter/kg. As the half-life and the clearance of foscarnet in plasma correlated with changes in renal function, dosage adjustments must be made for patients with decreased renal function.